There Is No Darwin's Greatest Secret - Malec, Grzegorz (Filozoficzne Aspekty Genezy, 2023)
Review of: Mike Sutton, Nullius in Verba: Darwin’s Greatest Secret, Thinker Media [First Digital Edition], Kindle Edition 2014.